Pasteurella Multocida Type B In Malaysia: Characterisation, Immune Response And Protection In Vaccinated Buffaloes - Subramaniam, Chandrasekaran (1993)

(untitled)
A study on the characteristics of the Malaysian field and vaccine strains of Pasteurella multocida type B was conducted . In addition , the immunogenic potential of haemorrhagic septicaemia ( HS ) vaccines was evaluated in buffaloes . A total of 48 P. multocida isolates including the five HS vaccine strains were included in the study . Initial studies showed significant cross-protection in mice amongst the five vaccine strains . The 48 isolates , when subjected to biochemical tests had very little or no variability amongst them. Type-specific hyper immune sera were prepared in rabbits and buffaloes . The sera were then absorbed using antigens prepared from the 48 isolates . A series of serological tests were conducted using the pre- and post-absorbed sera and the antigen preparations . The protein profile of the five vaccine and five randomly selected field strains of this organism revealed that there appeared to be no variation amongst the field and vaccine strains . The antibody responses of buffaloes immunised with three conventional HS vaccines viz . , broth bacterin ( BB ) , alum-precipitated vaccine ( APV ) and oil adjuvant vaccine ( OAV ) and one experimental double emulsion vaccine ( DEV ) were determined by an enzyme-linked immunosorbent assay ( ELISA ) . Antibody levels were significantly higher in buffaloes immunised with the adjuvanted vaccines ( APV , OAV , DEV ) . Buffaloes immunised with BB alone were protected at 6 weeks but not at 12 weeks post-immunisation . Buffaloes immunised with APV were protected at 24 weeks but only partially at 52 weeks post-immunisation . On the other hand , buffaloes immunised with OAV or DEV were fully protected at 52 weeks but only partially at 76 weeks post-immunisation .There was also a positive relationship between the ELISA titres and protection in buffaloes .